Different is not deficient: contradicting stereotypes of Chinese international students in US higher education. Issue 1 (2nd January 2018) - Heng, Tang T.
Abstract : Mainland Chinese students form the largest international tertiary student population in the USA, yet most discourse around them tends to adopt a deficit perspective. Adopting a hybridized sociocultural framework, this qualitative study follows 18 Chinese undergraduates over one year to examine how challenges they face are influenced by sociocultural contexts and change over time. Findings reveal that Chinese students face challenges around relearning new language skills and communication styles, thinking like a 'Westerner', understanding new classroom expectations and sociocultural contexts, and finding balance between work and play. These challenges arise from the different school, societal, and cultural expectations in China versus the USA. Debunking stereotypes that Chinese international students are passive and needy, this study argues that they possess agency as evident in their responses to challenges faced and changes in their attitudes and behaviors over time. Findings aim to increase intercultural understanding between international students and staff and improve college policies that address students' needs.